An assessment of dust generation from ores - Petavratzi, Evaggelia (2006)
Dust from mining activities is produced from several unit operations and is often a serious problem to the industry, due to the influence it can have on human health and the safety record and productivity of a mine. So far, legislative parties and the industry have approached dust as an issue that needs to be controlled, only when a mining operation or process generates undesirable particulates. Nevertheless, new legislation and standards, such as the EU IPPC directive (Integrated Pollution Prevention and Control) and air quality strategies aim to drive mining companies to incorporate dust assessment planning that will be implemented through the whole life cycle of the mine. Mitigation and monitoring practices as well as health surveillance programs will need to be clearly defined.